3D CFD-DEM-IBM SIMULATIONS OF SAND PRODUCTION IN OIL WELLS - Rakhimzhanova, Aigerim (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Sand production is particularily prominent in sandstone reservoirs, which are common to observe in the majority of oil and gas fields. When sand particles start to erode from weak sandstone formations for different reasons, their impact could lead to the decline of the production flow rate and equipment degradation, which will results in a huge economical loss. In some cases, it results in the end of production life of a well and reservoir. The key to overcome this problem and achieve accurate prediction of sand production may lie in the understanding of the cause of sanding mechanism. The current numerical approaches to predict the sanding mechanism are based on continuum and non-continuum models. The majority of developed models are based on the continuum approach, while a few discontinuum-based (DEM – Discrete Element Method) have been developed in the last two decades. Sand production is a dynamic and continuous process, which starts from microscopic scales where the rock is discontinuous in nature. It is impossible to capture local discontinuous phenomena using continuum-based models. The DEM models can capture the interaction and motion of each sand grain, the failure micro mechanism in a dynamic process at micro and macro scales, which makes it possible to simulate the sanding phenomena. In this research the DEM is firstly used for the rock characterization, where a simple 3D bond contact model for cemented sandstone material is developed by modifying the previous existing JKR (Johnson-Kendall-Roberts) model for auto-adhesive silt size sand particles, and the model parameter is the bond strength in terms of the interface energy. The material properties of the synthetic sandstone specimens equivalent to the Ustyurt-Buzachi Sedimentary Basin core samples were reproduced for the numerical specimens and the triaxial compression test results show that the numerically simulated macroscopic response is in good agreement with the experimental results of the cemented sandstone. The main aim of this research is to develop the sample preparation procedure/method with physical perforation penetration and sand production modelling in a periodic cell and by developing and using the combined 3D CFD-DEM-IBM modelling techniques (CFD – Computational Fluid Dynamics; IBM – Immersed Boundary Method). The application of the IBM is proposed to simulate the complex interaction between the geometry of the cased horizontal well completion opening and the weakly cemented sandstone under the overburden pressure and drawdown. The capability of developed methods to capture sand arching, damage zone (due to the perforation penetration) and sanding mechanism (erosion near the perforation hole) due to the pressure drawdown are presented. This study shows the mechanism of sand production in a bottom-up approach in the first 0.1 sec of sanding initiation immediately after the perforation penetration in oil wells, which will help engineers to better understand the sanding mechanism at the micro levels and how the problem of sanding can eventually be overcome though better insight into the phenomenon.
Keywords: Computational Fluid Dynamics; CFD; Immersed Boundary Method; IBM; Research Subject Categories::TECHNOLOGY; type of access: embargo